Do psychological factors play a crucial role in sport performance? – Research on personality and psychological variables of athletes in Hungary - Gyomber, N.; Kovacs, K.; Lenart, A. (Cuadernos de Psicología del Deporte, 2016)
Contemporary research aims to investigate background factors that contribute to successful sport performance. Of these factors the psychological well-being and mental health status should be underlined that have gained a significant role, particularly in the frames of sport psychological counseling. The aim of the present study is to seek for interrelations of psychological variables and sport performance of young athletes, and to reveal what advantages might be utilized in younger ages to strengthen sport performance. No gender differences were found in sport performance; while age showed significant difference. The findings indicated differences of the investigated psychological variables by age and gender. Regression analyses were employed to test how psychological factors predict successful sport performance. The analyses strengthened the role of age and gender specific factors that should be considered during sport psychological counseling. The benefits should be highlighted in young age in order to ensure more successful performance in adulthood.